Methodology for evaluating Insite: Canada's first medically supervised safer injection facility for injection drug users - Wood, Evan (BioMed Central, 2004)
Many Canadian cities are experiencing ongoing infectious disease and overdose epidemics among injection drug users (IDUs). In particular, Human Immunodeficiency Virus (HIV) and hepatitis C Virus (HCV) have become endemic in many settings and bacterial and viral infections, such as endocarditis and cellulitis, have become extremely common among this population. In an effort to reduce these public health concerns and the public order problems associated with public injection drug use, in September 2003, Vancouver, Canada opened a pilot medically supervised safer injecting facility (SIF), where IDUs can inject pre-obtained illicit drugs under the supervision of medical staff. The SIF was granted a legal exemption to operate on the condition that its impacts be rigorously evaluated. In order to ensure that the evaluation is appropriately open to scrutiny among the public health community, the present article was prepared to outline the methodology for evaluating the SIF and report on some preliminary observations. The evaluation is primarily structured around a prospective cohort of SIF users, that will examine risk behavior, blood-borne infection transmission, overdose, and health service use. These analyses will be augmented with process data from within the SIF, as well as survey's of local residents and qualitative interviews with users, staff, and key stakeholders, and standardised evaluations of public order changes. Preliminary observations suggest that the site has been successful in attracting IDUs into its programs and in turn helped to reduce public drug use. However, each of the indicators described above is the subject of a rigorous scientific evaluation that is attempting to quantify the overall impacts of the site and identify both benefits and potentially harmful consequences and it will take several years before the SIF's impacts can be appropriately examined.